Analisa surface defect pada baja slab (Studi kasus di slab steel plant PT. Krakatau Steel-Cilegon) - N.H. Sari; I.W. Yatra (Dinamika Teknik Mesin, 2019)
The purpose of this case study is to analyze the surface defects that occur in slab steel. Investigations and observations have been made on slab steel. Surface defects that were investigated were obtained based on survey data in slab handling. The results show that frequent surface defects are transverse crack, corner transverse crack, corner crack, longitudinal crack, porous / blow hole, and oscillation mark. Further, the type of surface defect that often occurs in steel slab is the type of corner crack. It is due to sulfur and phosphorus content on the slab steel grade are higher.